Is driving under the influence of kava associated with motor vehicle crashes? A systematic review of the epidemiological literature - Iris Wainiqolo; Bridget Kool; Vili Nosa; Shanthi Ameratunga (Elsevier, 2015)
Abstract Objective: Kava is marketed as a herbal anxiolytic in several countries and is consumed recreationally in high doses in many indigenous Pacific and Australian Aboriginal communities. We reviewed the published literature examining the association (if any) between kava use and motor vehicle crashes (MVCs), MVC‐related injuries or driving performance. Methods: Search of MEDLINE, EMBASE, PsycINFO, CINAHL, Scopus, AMED, Australian Medical Index, Australian Transport Index and trials registries and injury journals up to August 2014. Results: No studies quantifying the effects of kava on MVCs or related injury were located. Four experimental studies using computer‐based driving simulation examined the effects of pharmacological doses of kavalactones on cognitive and visuomotor performance. While no statistically significant adverse changes attributable to kava were found, there was weak evidence of slowed reaction time. One study found the visuo‐motor performance on driving simulation to be significantly impaired when kava was consumed with alcohol. Conclusions: With equivocal evidence limited to experimental studies using simulated driving settings, the contribution of kava to MVCs is unknown. Implications: The gap in knowledge regarding the potential risk of injuries associated with therapeutic and recreational use of kava requires priority attention.